Dermoscopy in the diagnosis of mycosis fungoides - Olga G. Artamonova; Arfenya E. Karamova; Ekaterina V. Girko (Vestnik Dermatologii i Venerologii)
Mycosis fungoides is a primary epidermotropic T-cell lymphoma of the skin, characterized by the proliferation of small and medium-sized T-lymphocytes with cerebriform nuclei. Mycosis fungoides accounts for 60.6% of the total number of all cases of primary T-cell lymphomas of the skin. Diagnosis of mycosis fungoides remains a big challenge in dermatology: the average time for diagnosis from the onset of the disease is 5 years. The difficulty of differential diagnosis with chronic inflammatory dermatosis is due to the similarity of their clinical characteristics, especially in the early stages of the mycosis fungoides. The search for new methods aimed at early diagnosis of skin T-cell lymphoma is one of the most important tasks in dermatooncology. A number of morden studies aimed at assessing the capabilities of dermatoscopy as an additional method for diagnosing mycosis fungoides. Specific dermoscopic pattern of mycosis fungoides were identified: fine short linear vessels, orange-yellowish patchy areas and vascular structure resembling spermatozoa. Description of this dermoscopic pattern can influence the accuracy of diagnosis and timeliness of diagnosis, the prescription of effective methods of therapy in the early stages of the disease, improving the quality and increasing the life expectancy of patients. The article provides an overview of the most up-to-date information on the dermoscopic pattern of mycosis fungoides.